Assessment of nurses' knowledge, attitude and implementation of skin‐to‐skin care within the perinatal setting in Saudi Arabia: Survey study. Issue 4 (10th November 2022) - Al Mutair, Abbas; Almutairi, Wedad; Aljarameez, Faiza; Kay, Elbert; Rabanal, Rhea; Abellar, Katrina; Napaod, Aireen; Hawsawi, Abeer; Saha, Chandni; Ahmed, Gasmelseed Y.
Abstract: Aim: To evaluate knowledge, attitude and implementation of Skin‐to‐Skin Care (SSC) among nurses and to assess the implementation of SSC in the perinatal setting. Design: A cross‐sectional study design was implemented utilizing survey distributed among critical care paediatric and neonatal nurses. Methods: The data collection form was pre‐structured validated tool consisted of two main sections; socio‐demographic characteristics and Likert scale of 20 items covering four main domains in; knowledge, attitude, education and implementation of SSC. Results: The vast majority of the sample 91 (98%) were females with mean age and mean years of experience 33.5 ± 6.5 and 9.7 ± 6.5 years respectively. Almost half of them 45 (48.4%) work in obstetric and labor and delivery units. Correlation coefficient revealed a significant association between the total educational years of nursing degree and SSC. The results showed nurses with bachelor or master significantly more knowledgeable and skilled in implementing SSC compared to others.